A new approach for business process reconfiguration under uncertainty using Dempster-Shafer Theory. Issue 1 (31st December 2023) - Zidi, Slim; Ben Soussia, Tayssir; Hamani, Nadia; Benaissa, Mounir; Kermad, Lyes
Abstract : In an increasingly changing and uncertain market, adapting the supply chain to new changes requires reconfiguring supply chains processes to improve its performance. The decision-making process for the reconfiguration of supply chains must take into consideration the uncertainty and imprecision related to the judgments of the decision-makers. This paper deals with uncertainty in the decision-making process of supply chain reconfiguration using the Dempster-Shafer theory. An approach to reconfigure supply chain business processes under uncertainty is also proposed to improve the decision-making process for supply chain reconfiguration. The reconfiguration of the supply chain involves selecting the most appropriate configuration, process, actor and role that should be reconfigured in advance in order to optimise the reconfiguration using the Quality Function Deployment (QFD) and the Analytic Hierarchy Process (AHP) method. To reduce the imprecision and uncertainty related to the judgments and preferences of the decision-makers, the Dempster-Shafer theory is applied and, to validate the introduced approach, a case study is conducted.